2017
DOI: 10.18632/oncotarget.17959
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing identified genetic risk factors for asparaginase-related complications in childhood ALL patients

Abstract: Allergy, pancreatitis and thrombosis are common side-effects of childhood acute lymphoblastic leukemia (ALL) treatment that are associated with the use of asparaginase (ASNase), a key component in most ALL treatment protocols. Starting with predicted functional germline variants obtained through whole-exome sequencing (WES) data of the Quebec childhood ALL cohort we performed exome-wide association studies with ASNase-related toxicities. A subset of top-ranking variants was further confirmed by genotyping (N=3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 49 publications
2
36
0
3
Order By: Relevance
“…in Caucasians [47], diabetes mellitus [48], autoimmune diseases [49,50], endometriosis [45,51], and knee osteoarthritis [52,53]. A meta-analysis published in 2019 focusing only on renal cancer association studies also found no association between rs4778889 and rs11556218 and this disease [54].…”
Section: Discussionmentioning
confidence: 99%
“…in Caucasians [47], diabetes mellitus [48], autoimmune diseases [49,50], endometriosis [45,51], and knee osteoarthritis [52,53]. A meta-analysis published in 2019 focusing only on renal cancer association studies also found no association between rs4778889 and rs11556218 and this disease [54].…”
Section: Discussionmentioning
confidence: 99%
“…Case studies of unanticipated drug response or drug-induced morbidity have included PGx analysis and large-cohort studies have analyzed the prevalence of PGx alleles to estimate risk of adverse outcomes or nonresponse [93][94][95][96][97][98]. More recently, whole exome or genome sequencing studies have reported on PGx findings, though PGx results are not (yet) included in the list of recommended secondary findings [99].…”
Section: Implementation Sciencementioning
confidence: 99%
“…29 Also, a correlation between the SNPs in MYBBP1A, IL16 and SPEF2 with pancreatitis has been described. 35 Nevertheless, the impact of these variants is limited and predicting the risk of AAP and disease trajectories is not yet possible. 30 Since truncation of asparaginase therapy has been associated with reduced EFS, re-exposing AAP patients to asparaginase could be relevant to fully re-establish the probabilities of cure.…”
Section: Panel Discussionmentioning
confidence: 99%